Experimentally Induced Repeated Anhydrobiosis in the Eutardigrade Richtersius coronifer - Czernekova, Michaela; Jönsson, K Ingemar (PLoS One, 2016)
Tardigrades represent one of the main animal groups with anhydrobiotic capacity at any stage of their life cycle. The ability of tardigrades to survive repeated cycles of anhydrobiosis has rarely been studied but is of interest to understand the factors constraining anhydrobiotic survival. The main objective of this study was to investigate the patterns of survival of the eutardigrade Richtersius coronifer under repeated cycles of desiccation, and the potential effect of repeated desiccation on size, shape and number of storage cells. We also analyzed potential change in body size, gut content and frequency of mitotic storage cells. Specimens were kept under non-cultured conditions and desiccated under controlled relative humidity. After each desiccation cycle 10 specimens were selected for analysis of morphometric characteristics and mitosis. The study demonstrates that tardigrades may survive up to 6 repeated desiccations, with declining survival rates with increased number of desiccations. We found a significantly higher proportion of animals that were unable to contract properly into a tun stage during the desiccation process at the 5th and 6th desiccations. Also total number of storage cells declined at the 5th and 6th desiccations, while no effect on storage cell size was observed. The frequency of mitotic storage cells tended to decline with higher number of desiccation cycles. Our study shows that the number of consecutive cycles of anhydrobiosis that R. coronifer may undergo is limited, with increased inability for tun formation and energetic constraints as possible causal factors.
Keywords: Mitosis; Animals; velikost těla; mitotický index; Body Size; fyziologická adaptace; Tardigrada; Analysis of Variance; Mitotic Index; zvířata; Time Factors; mitóza; Adaptation, Physiological; Desiccation; vysoušení; časové faktory; analýza rozptylu